Pelatihan Kewirausahaan Anak Melalui Kegiatan Cooking Class Di Kelurahan Padang Bulan Medan Selayang - Diana Suksesiwaty Lubis; Lubis, Desy Irana Dewi (Yayasan Cita Cendikiawan Al Kharizmi, 2023)
The purpose of this activity is to introduce entrepreneurship to children, how to make something and process it and package it as attractive as possible and market it. This is done to introduce children to independence and communication and hone children's creativity. This activity was carried out in June 2023, the participants who attended were 30 children from the neighbourhood of Padang Bulan village. This research method is socialisation and practice. Explaining to children the introduction of tools and ingredients for cooking, making them directly involved in cooking activities. As a result, there were children who only listened and did not participate in the practice, and there were children who were very enthusiastic to be involved in all activities. This activity succeeded in making children to learn new things and hone their creativity, they know how to make delicious and marketable snacks.